Peran Dosen Mata Kuliah Pendidikan Pancasila dalam Meminimalisir Populasi Golput pada Pemilihan Umum - Rishi Suprianto; Netari Mulyawati; Iriansyah Iriansyah; Fitara Rahmania; Siti Hartati; Safaruddin Safaruddin (MAN 4 Kota Pekanbaru, 2026)
This manuscript is based on research using a qualitative literature observation method with the aim of understanding the phenomenon of the emergence of community groups who do not exercise their right to vote in general elections. The involvement of Pancasila lecturers in minimizing voting rights irregularities in elections is an important topic in this research. Various methods that have been implemented by lecturers in teaching Pancasila courses are carefully examined to see their impact on achieving this research objective. This research concludes that by strengthening Pancasila values, students are encouraged to become active and intelligent voters, thereby reducing the number of lost voting rights in general elections. The role of lecturers in minimizing abstentions is implemented through activities such as: Voter Education, Internalization of Pancasila Values, Building Political Literacy, Encouraging Active Participation as Agents of Change, Overcoming Political Apathy, Holding Discussions and Substantive Education.